2017
DOI: 10.1021/acsnano.7b02449
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer and Orbital Level Alignment at Inorganic/Organic Interfaces: The Role of Dielectric Interlayers

Abstract: It is becoming accepted that ultrathin dielectric layers on metals are not merely passive decoupling layers, but can actively influence orbital energy level alignment and charge transfer at interfaces. As such, they can be important in applications ranging from catalysis to organic electronics. However, the details at the molecular level are still under debate. In this study, we present a comprehensive analysis of the phenomenon of charge transfer promoted by a dielectric interlayer with a comparative study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
113
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(133 citation statements)
references
References 60 publications
8
113
0
5
Order By: Relevance
“…Reference experiments with pentacene. Previous studies of pentacene on Ag(001) have shown the energy-level alignment to be such that the LUMO is aligned with the Fermi energy and consequently partially occupied with an estimated charge of 0.7 electrons 35 . Any charge transfer-related magnetism is hindered by the substrate: the LUMO is substantially broadened by hybridization with the metal, and the high level of screening reduces electron correlations 36,37 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Reference experiments with pentacene. Previous studies of pentacene on Ag(001) have shown the energy-level alignment to be such that the LUMO is aligned with the Fermi energy and consequently partially occupied with an estimated charge of 0.7 electrons 35 . Any charge transfer-related magnetism is hindered by the substrate: the LUMO is substantially broadened by hybridization with the metal, and the high level of screening reduces electron correlations 36,37 .…”
Section: Resultsmentioning
confidence: 96%
“…The presence of this Kondo resonance is further proof of the decoupling effect that the "pentacene functionalization" at C-2 and C-3 with sp 3 carbon atoms brings about. If that were not the case, a broader LUMO level and reduced electron correlations would cause an equal population of spin up and spin down LUMO orbitals 36,37 , resulting in no net spin and no Kondo peak, as occurs with pristine pentacene 35 . On the other hand, the Kondo resonance still implies a minor molecule-substrate coupling, since it relates to the screening of the molecular spin by the substrate electrons and would thus be absent for a more efficient decoupling as observed for pentacene on an insulating MgO buffer layer.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the theoretical momentum maps for 5A have already been experimentally confirmed by analyzing the photoelectron angular distribution within ARPES experiments. 52 , 53 , 56 58 Using the technique of photoemission tomography, 59 such measurements are being planned also for DHTA n in future.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Despite the potential impact of this approach, only af ew molecules have been shown to efficiently donate (or accept) significant charge,t his quality being related to the presence of donor (acceptor) moieties in their structures.…”
mentioning
confidence: 99%